Circular RNA EFR3A promotes nasopharyngeal carcinoma progression through modulating the miR-654-3p/EFR3A axis: CircEFR3A promotes NPC - Jiang, Pan; Xia, Binghua (Cellular and Molecular Biology, 2023)
Nasopharyngeal carcinoma (NPC) originates from the nasopharyngeal epithelium. hsa_circ_0135761 (circEFR3A), a newly identified circRNA, presented elevation in NPC via high-throughput sequencing. This study aimed to clarify the molecular mechanism of circEFR3A in the carcinogenesis of NPC. Based on RT-qPCR, subcellular fractionation, RNase R digestion and actinomycin D assays, we evaluated circEFR3A expression characteristics in NPC cells. We found that the circEFR3A was located in the cytoplasm of NPC cells, presented upregulation and stably expressed in NPC cells. Loss-of-function assays clarified the effects of circEFR3A on NPC cell malignant behaviors. The results demonstrated that circEFR3A knockdown facilitated NPC cell apoptosis but repressed NPC cell proliferation and migration. Furthermore, the regulatory mechanism of circEFR3A in NPC was explored. Bioinformatics and mechanism experiments revealed that cicrEFR3A positively modulated EFR3A by competitively binding with miR-654-3p in NPC cells. Additionally, rescue assays showed that the suppressive effects of cicrEFR3A knockdown on NPC cell proliferation, migration and apoptosis were countervailed by EFR3A upregulation. Xenograft tumor-bearing mouse models were established to investigate the role of cicrEFR3A in NPC tumorigenesis in vivo, and the results indicated that circEFR3A silencing suppressed tumor growth in mice. In conclusion, circEFR3A is highly expressed and functions as an oncogene in NPC progression. circEFR3A facilitates NPC cell proliferation and migration by binding to miR-654-3p to upregulate EFR3A, providing a potential new direction for seeking therapeutic plans for NPC.